The Research Progression and Clinical Significance of Circular RNAs in Head and Neck Cancers - Wang, Danhui (Biomed Res Int, 2020)
With rapid development of science technique and molecular research, a large number of circular RNAs (circRNAs) were discovered. CircRNAs that are a heterogeneous endogenous group of non-coding RNA not only are abundantly and diffusely expressed in mammals but also participate in many biological processes, such as in tumor ingenuity and progress. CircRNAs have rarely open reports in the head and neck cancers (HNC), which are an aggressive malignant tumor with unsatisfactory overall survival rates. The diagnostics and treatments continue to improve while the survival rate of HNC patients has no more obvious improvement. Recent studies that are aimed at exploring the molecular mechanisms of occurrence and progression of circRNAs in HNC provide a valuable insight into potential novel diagnostic and therapeutic approaches. In this review, we summarize the increasing number of published researches on the research progression of circRNAs in HNC, as well as their possible clinical implications on HNC.